2003
DOI: 10.1038/sj.bjc.6601250
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear shift of hnRNP K protein in neoplasms and other states of enhanced cell proliferation

Abstract: The heterogeneous nuclear ribonucleoprotein K (hnRNP K), is a ubiquitously expressed protein that interacts with signal transducers, proteins that modulate gene expression and selective RNA and DNA motifs. K protein is modified in response to extracellular signals and directly regulates rates of transcription and translation. We used serum-treated hepatocyte culture, liver after partial hepatectomy and hepatic neoplasms as systems to compare expression, subcellular distribution and tyrosine phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 46 publications
6
55
0
1
Order By: Relevance
“…42 A physical interaction of b-catenin/TCF-4 complex with several hnRNPs, involved in the regulation of pre-mRNA splicing, has been described 43 and some types of alternative splicing are considered to promote prostate cancer progression. 44,45 As hnRNP K is involved in the regulation of transcription and translation of specific mRNAs depending on its phosphorylation status, 10,46 we propose a model where AKT directly controls hnRNP K and b-catenin phosphorylation and their transcriptional activities leading to NED (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A physical interaction of b-catenin/TCF-4 complex with several hnRNPs, involved in the regulation of pre-mRNA splicing, has been described 43 and some types of alternative splicing are considered to promote prostate cancer progression. 44,45 As hnRNP K is involved in the regulation of transcription and translation of specific mRNAs depending on its phosphorylation status, 10,46 we propose a model where AKT directly controls hnRNP K and b-catenin phosphorylation and their transcriptional activities leading to NED (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…7 The importance of immuno-histological detection of NED in prostatic adenocarcinoma with respect to disease at presentation and Gleason grade is gaining acceptance, and a correlation of immunohistochemically detected markers of neuroendocrine differentiation with clinical predictors of disease progression in prostate cancer has been reported. 8 Using proteomic analysis of the nuclear matrix, we previously reported that hnRNP K, a member of the hnRNP family with pleiotropic functions, [9][10][11][12] was overexpressed in PC specimens with involvement of seminal vesicles and that its expression level was closely correlated with Gleason score and poor prognosis. 13 It has been recently demonstrated that hnRNP K regulates the expression of AR by a posttranscriptional mechanism 14 and that NE cells in malignant prostatic tissues show no androgen receptors.…”
mentioning
confidence: 99%
“…These findings are consistent with the results of the RNA EMSAs and, taken together with the mRNA half-life measurements, strongly indicate that hnRNP E1, as part of a 3=-UTR RNP complex, plays an important function in the active stabilization of eNOS mRNA. hnRNP E proteins are known to shuttle between the nucleus and cytoplasm, with functional consequences for the translational efficiencies of their target mRNAs (e.g., ␣2-globin mRNA) (51)(52)(53)(54). Indeed, chromatin immunoprecipitations (ChIPs) against hnRNP E1 revealed specific E1 enrichment at eNOS P2/P3/P4 elements compared to the amount at the eNOS promoter (data not shown).…”
Section: Fig 3 Enos-stabilizing Rnp Complexes Contain Hnrnp E1 (A) Imentioning
confidence: 99%
“…Heterogeneous nuclear ribonucleoproteins (hnRNPs) are predominantly nuclear RNA-binding proteins that have been implicated in diverse molecular and cellular functions, including chromatin remodeling, transcription, splicing and translation (14,(25)(26)(27)(28). It acts as a docking platform to integrate signaling cascades by facilitating cross-talk between kinases and factors that mediate nucleic acid-directed processes (29).…”
Section: Identification Of Target Protein For Intracellular Antibody-mentioning
confidence: 99%